2021
DOI: 10.1177/19417381211028212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Face Mask Use on Objective and Subjective Measures of Thermoregulation During Exercise in the Heat

Abstract: Background: While increased face mask use has helped reduce COVID-19 transmission, there have been concerns about its influence on thermoregulation during exercise in the heat, but consistent, evidence-based recommendations are lacking. Hypothesis: No physiological differences would exist during low-to-moderate exercise intensity in the heat between trials with and without face masks, but perceptual sensations could vary. Study Design: Crossover study. Level of Evidence: Level 2. Methods: Twelve physically act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 29 publications
5
29
0
3
Order By: Relevance
“…The RPE was significantly higher in those wearing surgical masks (SMD 0.36, 95% CI 0.21–0.52; p < 0.01; I 2 = 30%), while no effect was observed in those with FFP2/N95 respirators ( p = 0.06) or cloth masks ( p = 0.21), as shown in Fig. 5 a. Additionally, 14 studies reported on dyspnea [ 12 , 25 , 37 – 39 , 43 , 48 , 50 , 52 56 , 60 ], five reported on fatigue level [ 3 , 18 , 40 , 41 , 47 ], and six reported on thermal sensation [ 3 , 18 , 40 , 47 , 56 , 57 ]. This meta-analysis establishes that wearing face masks during exercise results in significantly higher dyspnea (SMD 0.72), fatigue level (MD 1.34), and thermal sensation (SMD 0.67) in participants (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The RPE was significantly higher in those wearing surgical masks (SMD 0.36, 95% CI 0.21–0.52; p < 0.01; I 2 = 30%), while no effect was observed in those with FFP2/N95 respirators ( p = 0.06) or cloth masks ( p = 0.21), as shown in Fig. 5 a. Additionally, 14 studies reported on dyspnea [ 12 , 25 , 37 – 39 , 43 , 48 , 50 , 52 56 , 60 ], five reported on fatigue level [ 3 , 18 , 40 , 41 , 47 ], and six reported on thermal sensation [ 3 , 18 , 40 , 47 , 56 , 57 ]. This meta-analysis establishes that wearing face masks during exercise results in significantly higher dyspnea (SMD 0.72), fatigue level (MD 1.34), and thermal sensation (SMD 0.67) in participants (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Overall, 22 studies used a progressive exercise test [ 3 , 12 , 14 , 18 , 24 , 26 , 30 , 35 , 36 , 39 , 41 , 43 – 45 , 48 , 50 , 51 , 53 – 55 , 59 , 60 ], while 19 employed the steady-state constant exercise test [ 13 , 15 , 25 , 29 , 31 , 34 , 37 , 38 , 40 , 42 , 46 , 47 , 49 , 52 , 56 58 , 61 , 62 ], and two used interval exercise tests [ 28 , 32 ]. Moreover, one study used a resistance exercise test [ 33 ], and one used a sit-to-stand test [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Each domain was rated as "low risk of bias," "high risk of bias," and "some concerns" for the reported outcomes, and the overall risk of bias judgment: low risk of bias-all domains showed a low risk of prejudice; some concerns: in at least one domain for this outcome but not being at high risk of bias for any domain, and high risk of bias-when in at least one domain for this outcome or have some concerns for multiple domains in some way that substantially reduces confidence in the result. 2021;Rojo-Tirado et al, 2021;Ryu and Jong-Geun, 2021;Slimani et al, 2021;Tornero-Aguilera et al, 2021;Yoshihara et al, 2021;Zhang et al, 2021;Cabanillas-Barea et al, 2022;Jesus et al, 2022;Ng et al, 2022;Rosa et al, 2022;Steinhilber et al, 2022) met all the eligibility criteria and were included in the review. Two additional studies (Shaw et al, 2020;Otsuka et al, 2022) were found from other sources (e.g., references from included studies, and publications founded in other reviews).…”
Section: Studies' Quality Appraisalmentioning
confidence: 99%
“…All studies presented a control condition (i.e., no face mask wearing). The samples were composed mostly by healthy (Zimmerman et al, 1991; Roberge (Fikenzer et al, 2020;Shaw et al, 2020;Wong et al, 2020;Ade et al, 2021;Epstein et al, 2021;Kampert et al, 2021;Yoshihara et al, 2021), healthy trained (Rojo-Tirado et al, 2021;Ng et al, 2022) resistance-trained (Rosa et al, 2022), and healthy sedentary (Otsuka et al, 2022) adults; athletes (Dantas et al, 2021;Egger et al, 2021;Tornero-Aguilera et al, 2021) and amateur soccer players (Modena et al, 2021). The sample size varied from six (Otsuka et al, 2022) Among the types of exercise, the participants performed on cycle ergometer (n = 14) (Zimmerman et al, 1991;Fikenzer et al, 2020;Lässing et al, 2020;Shaw et al, 2020;Ade et al, 2021;Doherty et al, 2021;Egger et al, 2021;Epstein et al, 2021;Mapelli et al, 2021;Zhang et al, 2021;Jesus et al, 2022;Ng et al, 2022;Otsuka et al, 2022;Steinhilber et al, 2022), walking in treadmill (n = 13) (Roberge et al, 2010;Roberge et al, 2012a;Roberge et al, 2012b;Chen et al, 2016;Kim et al, 2016;Wong et al, 2020;Bar-On et al, 2021;…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation